Evaluasi Kinerja Jaringan Saluran Irigasi - Marhayu Saadatun Nubuwah; Virgo Trisep Haris; Lusi Dwi Putri (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
Irrigation is the provision, regulation and disposal of water for agriculture and fisheries needs. In the artificial lake area located in Lembah Sari Village, the main source of water for the community's fishery needs comes from the Danau Buatan irrigation channel network that drains water to the community's fishing ponds. In the use of irrigation channels that have been going on for a long time, it is believed that there are channel damage and lack of water, especially in the fishing pond section at 285 meters. The purpose of this study was to determine the causes of water shortages for fishing ponds and to evaluate the performance of the Danau Buatan irrigation canal network. The analytical method used in this study is to find the value of the effectiveness and efficiency of the irrigation canal network, the comparison of the planned discharge with the water discharge in the channel. The results of the research that have been done with the efficiency value obtained are 50%, the results of the study are different from the plan efficiency value, namely 65% and the effectiveness of the channel that drains water to fishery ponds, namely 41.8%, the effectiveness value of the irrigation channel is low. The use of irrigation water networks is not optimal and there is an overflow of the intake or water catchment structures and some channel points that cause water shortages to be channeled into fishery ponds.